Experimental investigation of an enhanced transpired air solar collector with embodied phase changing materials. (15th February 2022) - Bejan, Andrei - Stelian; Croitoru, Cristiana; Bode, Florin; Teodosiu, Cătălin; Catalina, Tiberiu
Abstract: Transpired solar air collectors are cost-benefit optimized systems, increasingly used nowadays to heat or to preheat the fresh air needed inside buildings. The most important issue regarding the implementation of solar collectors is determined by the fact that these systems can be used only when solar radiation is available because of their lack of thermal mass. Phase changing materials (PCM) are widely studied in the recent years in different applications given their capacity of storing large quantities of latent thermal energy. The aim of the present paper is to study through an experimental approach, an innovative, enhanced transpired air solar collector with integrated PCM which has the benefit to increase its operating period and its overall efficiency. The data achieved experimentally shows that, by implementing RT35 organic PCM (paraffin) within a real scale solar collector, the maximum increase in temperature will be higher by 8.8% while its coefficient of performance will by 10.6% higher. Moreover, the useful operating time (when the coefficient of performance has values above 1) of the solar collector without PCM is 434 min, while in the case of the collector with PCM it is 937 min, resulting in a longer operation period of 110% (∼8 h more). Furthermore, the average coefficient of performance of the solar collector without embedded PCM is 6.6, while the average coefficient of performance of the solar collector with embedded PCM is 7.3 (10.6% higher). The main conclusion of the current study is that the innovative approach of PCM integration within solar air collectors can increase the overall efficiency of the system, the number of operating hours and even the temperature difference between ambient and exhaust air.